2018
DOI: 10.1111/prd.12239
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal complications with obesity

Abstract: The purpose of this paper was to identify and summarize current evidence describing periodontal complications associated with obesity. Electronic searches supplemented with manual searches were carried out to identify relevant systematic reviews. Identification, screening, eligibility, and inclusion of studies were performed independently by two reviewers. A MeaSurement Tool to Assess systematic Reviews (AMSTAR) was used to assess the quality and risk of bias of the included reviews. From 430 titles and abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 168 publications
4
98
2
3
Order By: Relevance
“…Being the most studied inflammasome in clinical diseases, NLRP3 has been implicated as having a role in several inflammatory and autoimmune diseases, including atherosclerosis, diabetes mellitus, obesity and rheumatoid arthritis, all of which are diseases known for their clinical association with periodontal disease . The data indicate that in these four conditions there is a dysregulation of the inflammatory response that is partly driven by NLRP3 .…”
Section: Inflammasomes and Disease Pathogenesismentioning
confidence: 99%
“…Being the most studied inflammasome in clinical diseases, NLRP3 has been implicated as having a role in several inflammatory and autoimmune diseases, including atherosclerosis, diabetes mellitus, obesity and rheumatoid arthritis, all of which are diseases known for their clinical association with periodontal disease . The data indicate that in these four conditions there is a dysregulation of the inflammatory response that is partly driven by NLRP3 .…”
Section: Inflammasomes and Disease Pathogenesismentioning
confidence: 99%
“…Another important factor in periodontitis etiology is obesity . Metabolic and non‐metabolic complications due to obesity are becoming more prevalent, yet our understanding of the mechanisms still lags behind.…”
Section: Introductionmentioning
confidence: 99%
“…Suvan et al in a systematic review reported a positive relation between obesity and periodontitis [31], confirmed in a very recent review, showing that obese subjects were more prone to periodontal disease onset compared to normal-weight subjects, regardless of age and gender [34] The potential mechanism underlying the putative mutual relationship between obesity and periodontitis may be related to low-grade inflammation.…”
Section: Potential Etiopathogenic and Molecular Links Between Obesitymentioning
confidence: 93%
“…In the systematic review results of Papageorgiou et al, after the periodontal treatment, no statistically significant differences were found between obese and normal-weight in relation to most of the periodontal parameters [30] Suvan et al reported in a systematic review inconsistent evidence of different clinical responses to non-surgical periodontal therapy in obese subjects compared to nonobese ones [30,31].…”
Section: Impact Of Periodontal Treatment On Obesitymentioning
confidence: 96%